Pragmatic-Discursive Strategies in Writings of Provisional Qualification and Defense in Oral Tria - CERVERA RODRÍGUEZ, ÁNGEL; TORRES ÁLVAREZ, JOSÉ (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The purpose of this research is to explain how pragmatic and dialectical strategies works in forensic discourse and to describe the communicative interaction between the prosecution and the defense in order to determine how the prosecution and the defense use these strategies to persuade the judge about the innocence or the culpability of the accused. The corpus is based on the first statements provided by the prosecution and the defense during an oral trial held in the Criminal Courts of Barcelona in 2010. To achieve this objective, we have proceeded to identify the linguistic components and the dialecti- cal-argumentative indicators that the parties use in their interventions, following a meth- odology based on pragma-dialectic theory, ethnomethodology, argumentation and (dis) courtesy. Among the results, the nominalization, the lexical and grammatical recurrence and the personal deictic indicators and discursive operators stand out. These strategies are joined by those that derive from the image projected by each part where courtesy or discourtesy comes into play